P‐61: Distinguished Poster: Research on Parameter Extraction of Thin‐Film Transistors Based on Swarm Intelligence - Liu, Peng; Liu, Bailing; Feng, Jing; Wang, Zhichong; Chang, Chuanchuan; Zhang, Qian; Zhang, Han; Liu, Dong; Guo, Xu; Zhang, Xin; Liu, Xingyao; Yuan, Guangcai (SID International Symposium Digest of technical papers, 2023)
Automatic parameter extraction of RPI Model for Polysilicon Thin‐Film Transistors is achieved by genetic algorithm(GA) and Particle swarm optimization(PSO) algorithm, and the solution of two algorithms are compared. Furthermore, mutual learning particle swarm optimization (MLPSO) algorithm is proposed, which simplifies the complex manual processes and the empirical calibration, and achieves accurate parameters extraction.